Game changers in labour law shaping the future of work - Aleksynska, Mariya (Wolters Kluwer, 2018)
Game Changers in Labour Law' is pursued in the spirit and with the methods of the late Emeritus Professor Roger Blanpain (1932?2016), a great reformer who continuously searched for key challenges in the world of work and looked as far as possible into the future, engaging in critical reflection and rethinking the design of labour law. While seeking to identify the main game changers, the authors explore new pathways and answers which may help to understand and shape the future of work. This book provides full and integrated insight into labour law and industrial relations
"Volume derives from an international conference organized by the Institute for Labour Law at the University of Leuven, Belgium in November 2017"-- Page 4 of cover
Includes bibliographical references
Keywords: Arbeitsrecht; Labor laws and legislation / Congresses; Konferenzschrift -- 03.11.2017-04.11.2017 -- Löwen